2022
DOI: 10.1186/s13018-022-03192-4
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant septic arthritis of the hip joint and femoral head avascular necrosis in patients with recent COVID-19 infection: a cautionary report

Abstract: Purpose At present, concomitant avascular necrosis (AVN) of femoral head and septic arthritis (SA) as a sequel of COVID-19 infection has yet not been documented. By large-scale use of life-saving corticosteroids (CS) in COVID-19 cases, our aim is to warn of the occurrence of hip joint infection in these patients. Methods We report a series of five cases in which patients developed septic arthritis concomitant with AVN after being treated for COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 26 publications
1
24
0
4
Order By: Relevance
“…Reporting the details on the severity of the disease and the need for ICU admission varied among the included reports. The details of the medical management were mentioned in seven reports [ 19 21 , 23 , 25 , 29 , 30 ], which included steroids, antivirals, antibiotics, biologics, and anticoagulants. In all reports, corticosteroids were used in the management plan except for one [ 15 ], where no steroids were used for any of the patients.…”
Section: Resultsmentioning
confidence: 99%
“…Reporting the details on the severity of the disease and the need for ICU admission varied among the included reports. The details of the medical management were mentioned in seven reports [ 19 21 , 23 , 25 , 29 , 30 ], which included steroids, antivirals, antibiotics, biologics, and anticoagulants. In all reports, corticosteroids were used in the management plan except for one [ 15 ], where no steroids were used for any of the patients.…”
Section: Resultsmentioning
confidence: 99%
“…The number of reports of CRONJ in other bones is slightly higher. Most notably knee 6 , 7 , 14 , 15 , hip 14 , 16 , femoral head 16 - 20 , and spine 21 . General musculoskeletal manifestations have also been reported 22 - 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the prevalence of RF and ACPA, largely inconsistent results were found, precluding the possibility to draw conclusions. Interestingly, besides arthralgia or inflammatory rheumatic diseases, a few cases of avascular necrosis of the femoral head or of transient osteoporosis of the hip have been described, suggesting potential vascular implications caused by the endothelial dysfunction induced by SARS-CoV-2 [30,87,88]. The early recognition of patients at higher risk of developing post-COVID-19 musculoskeletal diseases could lead to a better treatment of these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Ardakani et al described 5 patients developing septic arthritis with concomitant avascular necrosis of the femoral head, on average 42 days after the infection [30], while performing 18F fluorodeoxyglucose (FDG) positron emission tomography (PET) on 13 post-COVID-19 patients, Kiatkittikul et al showed radiotracer uptake in the skeletal muscle of 8 patients (62%), compatible with myositis [50].…”
Section: Other Musculoskeletal Inflammatory Conditions Of Rheumatolog...mentioning
confidence: 99%